2012
DOI: 10.1016/j.ijpsycho.2011.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence for different effects of working memory load on interference control in adolescents than adults

Abstract: The present study investigated how the development of interference control is influenced by the development of working memory (WM) capacity during adolescence. In a dual-task, 17 adolescents (12-16 years) and 19 adults (18-48 years) performed a gender word-face Stroop task, while WM-capacity was manipulated by a concurrently performed N-back task. Behavior (reaction times, % errors and % misses) and event-related potentials associated with the detection (N450) of the Stroop conflict and response selection (sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 74 publications
2
7
0
Order By: Relevance
“…The P3 amplitude decreased with increasing memory load, reflecting reallocation of cognitive resource from the matching phase to memory maintenance phase [27], [39]. In addition, we also found that the increase in working memory load was associated with a decrease of the N1 amplitude, which was in agreement with the N1 tendency in previous ERP studies [40][41]. In addition, similar results were also observed in fMRI studies [42][43].…”
Section: Discussionsupporting
confidence: 91%
“…The P3 amplitude decreased with increasing memory load, reflecting reallocation of cognitive resource from the matching phase to memory maintenance phase [27], [39]. In addition, we also found that the increase in working memory load was associated with a decrease of the N1 amplitude, which was in agreement with the N1 tendency in previous ERP studies [40][41]. In addition, similar results were also observed in fMRI studies [42][43].…”
Section: Discussionsupporting
confidence: 91%
“…Most studies did not have enough sample size and only two studies stated the psychometric properties of the measures used (Hagmann‐von Arx et al, 2016; Palluel et al, 2010). Six articles had better comparability among participants by controlling for the selection bias (Getchell and Whitall, 2003; Hagmann‐von Arx et al, 2016; Otte and van Mier, 2006; Reilly et al, 2008; Schaefer et al, 2015; Spronk and Jonkman, 2012). As per criteria proposed in Table 1, very few studies addressed most of the methodological issues (Anderson et al, 2011; Hinton and Vallis, 2015; Reilly et al, 2008; Schaefer et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Almost all studies used appropriate tasks except two -holding a glass of water and carrying a tray while walking or reaching -that are classified as complex single rather than dual tasks in the literature (McIsaac et al, 2015). Single tasks were equated by only eleven studies (Anderson et al, 2011;Hinton and Vallis, 2015;Irwin-Chase and Burns, 2000;Krampe et al, 2011;Rattat, 2010;Reilly et al, 2008;Schaefer et al, 2008;Sebastian and Hernandez-Gil, 2013;Spronk and Jonkman, 2012;Sun et al, 2013), two of which did not adjust or equate both single tasks (Krampe et al, 2011;Sebastian and Hernandez-Gil, 2013). Only eleven studies analyzed the DT effect using DTC (five: absolute DTC, six: proportional DTC) (Abbruzzese et al, 2014;Anderson et al, 2011;Boonyong et al, 2012;Gautier and Droit-Volet, 2002;Krampe et al, 2011;Miller et al, 1991;Otte and van Mier, 2006;Palluel et al, 2010;Reilly et al, 2008;Schaefer et al, 2008;Sebastian and Hernandez-Gil, 2013) and rest of them only used statistical methods to estimate the age effect (ANOVA).…”
Section: Clear Instructionsmentioning
confidence: 99%
“…The American Academy of Pediatrics recommends limiting media exposure in children to 2 h per day or less based on findings that elevated media use is associated with poor physical, cognitive, and social development and academic underperformance in children (Johnson et al, 2007; Junco, 2011; Junco and Cotten, 2011, 2012; Ozmert et al, 2002). From a neurodevelopmental standpoint, the cortex does not attain full capacity to manage interference until late adolescence/young adulthood (Giedd, 2012; Hagen and Hale, 1974; Harnishfeger and Bjorklund, 1994; Leon-Carrion et al, 2004; Spronk and Jonkman, 2012), which makes neural systems all the more prone to the negative impacts of heightened exposure to interference. Indeed, a recent study showed that teenagers intentionally engage with sources of interference, such as texting and Facebook, even in an observed study environment, which ultimately was associated with poor outcomes on their academic learning (Rosen et al, 2013).…”
Section: External Interference Resolution Across the Lifespanmentioning
confidence: 99%